Nerve Regeneration by Shock Wave Detected through Analysis of Stroke Patientsâ€™ Walking - Lee, Jung-Ho (International Journal of Engineering and Technology, 2019)
The purpose of this study was to investigate the effects of extracorporeal shock wave therapy to reduce spasticity during walking through nerve regeneration. The subjects of this study were 20 patients who were treated for stroke in a rehabilitation hospital. They were then randomly divided into an experimental group and a control group. The control group (n = 10) underwent a normal type of proprioceptive neuromuscular facilitation therapy, while the experimental group (n = 10) underwent a normal type of proprioceptive neuromuscular facilitation therapy and then extracorporeal shock wave therapy. The timed up and go test was used to evaluate the gait functions and dynamic balancing of the subjects. The modified Ashworth scale was used in this study to measure the spasticity of the subjects. Dartfish software was used to measure the angles of the ankle joints. Extracorporeal shock wave therapy was applied 700 times to the middle of the calf muscles of the affected side and 700 times to the musculotendinous junction of the calf muscles. The stimuli were applied to the sites to be treated for a total of 1,400 times at 3 Hz and 0.129 mJ/mm2. There was a statistically significant difference between pre-test and post-test of timed up and go in all groups. There was a statistically significant difference between pre-test and post-test of ankle joints angle in all groups. Also, the results of AJA assessment was a statistically significant difference between EX and Con groups. In conclusion, the extracorporeal shock wave therapy can reduce spasticity during walking through nerve regeneration.Â Â